Improving water supply systems efficiency: a methodology for optimal control of variable-speed pumps - Coelho, Bernardete (2020)
Nowadays, the major expenses in water supply systems (WSSs) are related to energy consumption. Pump stations usually represent the major portion of total energy costs. Generally, in most WSSs, the pump stations operations are only based on the pumps on/off, without taking advantage of variable-speed equipment. The pumps are switched on when the tanks, responsible for supplying certain populations, reach their minimum levels. These pumps are only switched off when the tanks reach their maximum levels. In the cases where variable-speed equipment is used, planned control strategies are almost always missing. The introduction operational pump schedules adapted to the energy prices variation and to the consumption patterns of the populations can optimise pump stations operations, minimising energy costs significantly. However, the process of finding the best pump pattern can present difficulties due to the complexity of some WSSs (multiple pumps, multiple reservoirs, nonlinear behaviour of the systems, etc.). A methodology for variable-speed pumps control is presented in this work. With the aim of test this methodology and apply distinct algorithms for the pumps schedules optimisation, a computational tool was developed. The tool consists on an automatic connection between the hydraulic simulator EPANET 2.0 and the optimisation algorithms, providing, after multiple iterations and evaluations, an optimal pump pattern for a certain water supply network represented. Both gradient-based and meta-heuristic algorithms are used in this study in order to improve the energy efficiency of two distinct examples of network. Results of the hydraulic simulation of the networks with the optimal pump schedules are used to predict the future behaviour of the systems with this type of operation adjustment. Thus, it is possible to verify if the system requirements (such as, minimum pressures, tanks levels, consumers supply, etc.) are being attended. Optimisation results demonstrated that the pump schedules optimisation provides significant reductions on energy costs without compromising the proper operation of the systems.